Design of Print Creation System Based on Digitization. Issue 3 (February 2021) - Song, Yongjun; Liao, Xiayan
Abstract: In recent years, China's digital technology has been rapid development, the transformation and upgrading of traditional industries through digital technology is one of the current mainstream trends. In this context, a new concept of digital art is put forward, and the traditional art creation forms affected by this have been completely changed, which also includes print creation. However, there are still many deficiencies in the existing digital print creation system. Therefore, this paper puts forward the design and research of digital print creation system. This paper makes a detailed investigation on the main advantages of digital technology on print creation. Through the survey results, it can be seen that the use of digital technology can enrich the color and form, make the picture more realistic, enhance the artistic value, enhance the function application, create more efficient, and create more novel and so on. However, there are still some shortcomings in the existing creation system, such as poor painting effect, lack of originality and novelty. Therefore, this paper optimizes and improves the digital print creation system. The traditional inertia thinking is broken through genetic algorithm, and personalized optimization is carried out according to the characteristics of print creation, which not only simplifies the calculation steps, but also improves the calculation accuracy. In order to further verify the effectiveness of this method, this paper compares the traditional methods and analyzes the final synthesis effect. The experimental results show that the signal-to-noise ratio of the print image processed by this method is much higher than that of the traditional method, which proves the effectiveness of the proposed method.